The algorithmic management of work and its implications in different contexts - Sara Baiocco; Enrique Fernández-Macías; Uma Rani; Annarosa Pesole (European Commission, Joint Research Centre (JRC), 2022)
This paper provides a conceptual framework for the emerging phenomenon of algorithmic man-agement and outlines some of the implications for work, from work organisation to working condi-tions (job quality). The paper defines algorithmic management as the use of computer-programmed procedures for the coordination of labour input in an organisation and puts it into context to discuss its usage in both digital labour platforms and 'regular' workplaces and companies, exploring its implications and providing a few policy suggestions. The paper argues that while algorithmic man-agement should be understood as the digital evolution of certain pre-existing trends that have long characterised the organisation of economic activity, it is potentially disruptive. This is because it increases considerably the organisational ability of controlling complex economic and work pro-cesses, as it benefits from the massive capacity to collect, store and process information of digital technologies. In algorithmic management, these technological developments are combined and used for re-organising control and re-shaping power balances in the workplace. This paper contrib-utes to the growing academic and policy literature on algorithmic management, proposing a con-ceptual framework for empirical investigations and a basic compass for policy making in this area.
Keywords: 330; Algorithmic management; digitalisation; automation; digital labour platforms; work or-ganization; working conditions